In Vitro Hair Growth Promoting Effect of a Noncrosslinked Hyaluronic Acid in Human Dermal Papilla Cells. (31st October 2021) - Zerbinati, Nicola; Sommatis, Sabrina; Maccario, Cristina; Capillo, Maria C.; Di Francesco, Serena; Rauso, Raffaele; Protasoni, Marina; D'Este, Edoardo; Gasperina, Daniela Dalla; Mocchi, Roberto
Abstract : Dermal papilla cells (DPCs) are a source of nutrients and growth factors, which support the proliferation and growth of keratinocytes as well as promoting the induction of new hair follicles and maintenance of hair growth. The protection from reactive oxygen species (ROS) and the promotion of angiogenesis are considered two of the basal mechanisms to preserve the growth of the hair follicle. In this study, a noncrosslinked hyaluronic acid (HA) filler (HYDRO DELUXE BIO, Matex Lab S.p.A.) containing several amino acids was tested with in vitro assays on human follicle dermal papilla cells (HFDPCs). The experiments were carried out to investigate the possible protection against oxidative stress and the ability to increase the vascular endothelial growth factor (VEGF) release. The results demonstrated the restoration of cell viability against UVB-induced cytotoxicity and an increase in the VEGF secretion. These data demonstrate the capability of the product to modulate human dermal papilla cells, suggesting a future use in mesotherapy, a minimally invasive local intradermal therapy (LIT), after further clinical investigations.